Gestión administrativa en la empresa I.L.G.A (Importadora Lino Gamboa) Cia. Ltda de la Ciudad de Babahoyo - Melendez Martillo, Noreidy Mabel (2020)
The research arises as an initiative to cooperate in the good management and growth of the administrative activities carried out by the company I.L.G.A (Importadora Lino Gamboa) Cía. Ltda., Belonging to the city of Babahoyo, where the situational analysis was carried out. The methodology chosen for this work was the qualitative approach, which uses the collection of theoretical data for the interpretation process, it applies analytical procedures to address its object of study. This was done through the interview technique, where the opinions of the collaborators were obtained to obtain information about the administrative processes and the behavior they maintain as workers. The results achieved show the application of an inadequate administrative management within the branch, resulting in an inappropriate distribution of tasks and responsibilities to the company's employees, causing misuse of both material and human resources.